A systemic review on liquid crystals, nanoformulations and its application for detection and treatment of SARS – CoV- 2 (COVID – 19) - Rastogi A.; Singh A.; Naik K.; Mishra A.; Chaudhary S.; Manohar R.; Singh Parmar A. (My University, 2025)
The COVID-19 is a pandemic caused by the SARS-CoV-2 virus, has instigated major health problems and prompted WHO to proclaim a worldwide medical emergency. The knowledge of SARS-CoV-2 fundamental structure, aetiology, its entrance mechanism, membrane hijacking and immune response against the virus, are important parameters to develop effective vaccines and medicines. Liquid crystals integrated nano-techniques and various nanoformulations were applied to tackle the severity of the virus. It was reported that nanoformulations have helped to enhance the effectiveness of presently accessible antiviral medicines or to elicit a fast immunological response against COVID-19 virus. Applications of liquid crystals, nanostructures, nanoformulations and nanotechnology in diagnosis, prevention, treatment and tailored vaccine administration against COVID-19 which will help in establishing the framework for a successful pandemic combat are reviewed. This review also focuses on limitations associated with liquid crystal-nanotechnology based systems and suggests the possible ways to address these limitations. Also, topical advancements in the ground of liquid crystals and nanostructures established diagnostics (nanosensor/biosensor) are discussed in detail. © 2022 Elsevier B.V.